The susceptibility of Aedes albopictus skuse populations from human dwellings to major insecticides for vector control programmes in agricultural and non-agricultural areas / Wan Norafikah Othman - Wan Norafikah , Othman (2019)
Dengue, chikungunya and Zika are important mosquito-borne diseases transmitted by Aedes aegypti and Aedes albopictus. Aedes albopictus was selected to determine its susceptibility against major insecticides used for vector control programmes. The underlying mechanisms of metabolic resistance detected in Ae. albopictus populations had been revealed. The efficacy of a synergist, piperonyl butoxide (PBO) which was employed in combination with organochlorines and pyrethroids to enhance the potency of these insecticides had also been assessed. Since chemical controls are applied in both vector control strategies and agricultural pest management, study localities comprising both agricultural and non-agricultural areas were chosen. Initially, ovitrap surveillance was conducted to determine the mosquito species composition in which Ae. albopictus was the predominant container-breeder in all study areas. The first offspring generation of Ae. albopictus was subjected to both larval and adult mosquito bioassays. The susceptibility of Ae. albopictus larvae from dengue prone residential area against fenitrothion, fenthion, temephos, propoxur and permethrin was significantly different than larvae from different types of agricultural areas. Significant difference in the susceptibility of Ae. albopictus adults from residential areas with and without the history of fogging activities in comparison with adult mosquitoes from various types of agricultural areas were only observed against fenitrothion, propoxur and bendiocarb. From the enzyme microassays, the significant role of non-specific esterases (EST) in the metabolic resistance was exhibited in all populations of Ae. albopictus adults. At larval stage, only α-esterases activity was involved significantly in the metabolic resistance of Ae. albopictus from non-agricultural areas. The glutathione-S-transferases (GST) enzyme was significantly engaged in the metabolic resistance of Ae. albopictus adults from paddy cultivation area as well as larvae from almost all types of area. In terms of insensitivity of acetylcholinesterase (AChE), all populations of Ae. albopictus adults were still sensitive against propoxur while only larvae from oil palm plantation and fogging-free residential areas were still sensitive to the same carbamate. At larval stage of Ae. albopictus, mixed level of resistance against organophosphates and carbamates were associated with significant escalated activities of α-esterases and glutathione-Stransferases. Conversely, for Ae. albopictus adults, various levels of resistance against organochlorines, organophosphates and carbamates were correlated with significant increased activities of α-esterases, β-esterases, glutathione-S-transferases and insensitive acetylcholinesterase. Meanwhile, the combination of the synergist piperonyl butoxide (PBO) with dichlorodiphenyltrichloroethane (DDT) of organochlorines improved the susceptibility of several populations of Ae. albopictus adults from high resistance to incipient resistance. The pre-exposure of PBO prior to the selection of pyrethroids caused significant reduction of the median knockdown time (KT50) at 30 minutes of the exposure time in all populations of Ae. albopictus adults. In summary, since chemical control remains the most preferred and feasible tool of vector control approaches as well as in the agricultural pest management, continuous monitoring actions on the susceptibility of mosquito vectors against these insecticides are crucial to prevent the uncontrolled insecticide resistance development among mosquito populations. The important role of PBO in enhancing the efficacy of insecticides as presented in this study confirmed the utilization of synergist as one of the promising ways to delay and overcome the rise of insecticide resistance in mosquito vectors.